The IMPLEMENTATION OF THE HDP NEXUS IN EUROPEAN UNION HUMANITARIAN DIPLOMACY:: CASE STUDIES OF THE SAHEL AND HORN OF AFRICA REGIONS (2017–2024) - Yusuf, Rifqi Itsnaini; Ardiansah (Jurnal Hubungan Internasional Peradaban, 2026)
The traditional approach of separating humanitarian aid, development, and peace efforts has shown significant limitations in addressing complex and prolonged crises. The Humanitarian Development-Peace (HDP) Nexus has emerged as a new paradigm that seeks to integrate these three dimensions to achieve more effective and sustainable outcomes. The European Union, as one of the world's largest humanitarian and development donors, has adopted the Triple Nexus approach as an integral part of its humanitarian diplomacy strategy, particularly in the African context which faces multidimensional challenges including conflict, poverty, climate change, and political instability. This research employs a constructivist paradigm with qualitative approach and descriptive-analytical design, utilizing document analysis as the primary strategy. The findings reveal that while there is high-level political commitment and comprehensive policy frameworks, practical implementation still faces various structural and operational challenges. Institutional fragmentation within the EU architecture remains a major barrier to effective integration, while differences in organizational culture, operational procedures, and incentive systems create resistance to integrated approaches. In the African context, geopolitical complexity and institutional capacity limitations add dimensions of challenge that require more nuanced and adaptive approaches.